2002
DOI: 10.1073/pnas.052707599
|View full text |Cite
|
Sign up to set email alerts
|

Binding of rainbow trout sperm to egg is mediated by strong carbohydrate-to-carbohydrate interaction between (KDN)GM3 (deaminated neuraminyl ganglioside) and Gg3-like epitope

Abstract: KDN␣233Gal␤4Glc␤1Cer [(KDN)GM3] is a major (Ϸ90%) component of total gangliosides found in sperm of rainbow trout (Oncorhynchus mykiss) and was shown to be present prominently at the sperm head by immunochemical staining with its specific mAb kdn3G. Liposomes containing (KDN)GM3 adhere specifically to GalNAc␤4Gal␤4Glc␤1Cer (Gg3Cer)-coated plastic plates. Interaction between (KDN)GM3 and Gg3Cer was much stronger than that previously observed between Neu5Ac␣233Gal␤4Glc␤1Cer and Gg3Cer. (KDN)GM3-Gg3Cer interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 54 publications
0
29
0
1
Order By: Relevance
“…More subtle sperm selection occurring near the egg surface involves cell signalling systems: (i) sperm-activating peptides produced by the egg jelly coat of sea urchin eggs, speract and resact, induce sperm chemotaxis (Ward et al 1985, Cook et al 1994. Recently Wood et al (2003) have shown that these peptides induce calcium fluctuations in the flagellum, thereby controlling the vigour and nature of sperm motility; (ii) Yu et al (2002) have recently shown that trout spermatozoa adhere to the peri-micropylar region of the egg surface through specific cell-cell carbohydrate interactions; these activate protein kinase-related signal transduction mechanisms within the sperm head; and (iii) Iwamatsu et al (1997) found that linear swimming velocity is correlated with the ability of spermatozoa to enter the micropyle, a finding which relates to observations by Creech et al (1998) that fish sperm velocity increases under the influence of the signalling molecule, nitric oxide, produced by the eggs around the site of sperm entry. In their paper Wood et al (2003) commented that sea urchin sperm populations are heterogeneous in their response to speract; one subpopulation within the sample of spermatozoa was unable to respond because the calcium concentrations were already high.…”
Section: Sperm Motilitymentioning
confidence: 99%
“…More subtle sperm selection occurring near the egg surface involves cell signalling systems: (i) sperm-activating peptides produced by the egg jelly coat of sea urchin eggs, speract and resact, induce sperm chemotaxis (Ward et al 1985, Cook et al 1994. Recently Wood et al (2003) have shown that these peptides induce calcium fluctuations in the flagellum, thereby controlling the vigour and nature of sperm motility; (ii) Yu et al (2002) have recently shown that trout spermatozoa adhere to the peri-micropylar region of the egg surface through specific cell-cell carbohydrate interactions; these activate protein kinase-related signal transduction mechanisms within the sperm head; and (iii) Iwamatsu et al (1997) found that linear swimming velocity is correlated with the ability of spermatozoa to enter the micropyle, a finding which relates to observations by Creech et al (1998) that fish sperm velocity increases under the influence of the signalling molecule, nitric oxide, produced by the eggs around the site of sperm entry. In their paper Wood et al (2003) commented that sea urchin sperm populations are heterogeneous in their response to speract; one subpopulation within the sample of spermatozoa was unable to respond because the calcium concentrations were already high.…”
Section: Sperm Motilitymentioning
confidence: 99%
“…It has been shown in other cell types that the function of those ion channels is cholesteroldependent [40][41] and related to cholesterol-rich lipid rafts [42]. Subsequent binding to a carbohydrate epitope within the egg micropyle area is mediated by a specific ganglioside on the sperm surface [43] which is also a typical component of membrane rafts. Hence, both motility initiation and fertilization are at risk of being altered by cholesterol treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The trisaccharides (17,23,31) were synthesized in the same manner from the disaccharide precursors (12,18,27). Glycosylation of the disaccharides (12,18,27) with 2-O-acetyl-3,4,6-tri-O-benzyla-d-mannopyranosyl trichloroacetimidate (11) gave the protected trisaccharides (14,20,28), which were then subjected to deacetylation (15,21,29), reduction at the azido groups (16,22,30), and reductive debenzylation to give the desired trisaccharides (17,23,31). Large 3 J values were observed for the ring protons of the hinge units in all the synthesized diand trisaccharides, indicating the assumption of a 4 C 1 conformation by the corresponding hinge unit in solution.…”
Section: Resultsmentioning
confidence: 99%